Separation of Plasma Thromboplastin Antecedent from Kallikrein by the Plasma α(2)-Macroglobulin, Kallikrein Inhibitor - Harpel, Peter C. (1971)
Plasma thromboplastin antecedent (PTA, factor XI) is an important intermediate in the intrinsic coagulation system, and plasma kallikrein has been implicated as a mediator of the inflammatory process. Whereas their biologic activities are functionally distinct, their identity as separate entities in plasma has not been fully established, and the nature of their plasma inhibitors has not been completely characterized. A partially purified preparation containing the clotting, tosyl arginine methyl ester (TAMe) esterase and kinin-producing activities of these substances has been prepared by DEAE-cellulose chromatography of a Celite eluate obtained from acid-treated human plasma. These activities were not separable by acrylamide gel electrophoresis nor by isoelectric focusing, their pI being approximately 8.7. Human plasma α(2)-macroglobulin has been shown to inhibit the proteolytic activity of kallikrein and to inhibit partially its TAMe esterase activity. An α(2)-macroglobulin, PTA, kallikrein incubation mixture was separated by gel filtration chromatography. The α(2)-macroglobulin formed a high molecular weight complex with kallikrein and appeared in early chromatographic fractions. The PTA-clotting activity was not inhibited by the α(2)-macroglobulin; 64% of the initial PTA activity was isolated in later fractions free of kallikrein-induced kinin-like activity. In contrast, clotting, TAMe esterase, and kinin-forming activities were inhibited after gel filtration chromatography of an incubation mixture of these activities and partially purified C1̄ inactivator (C1 esterase inhibitor). Electrofocusing of an incubation mixture of an activated PTA, kallikrein preparation, and α(2)-macroglobulin resulted in the isolation of a PTA fraction free of kallikrein proteolytic activity, and with 4% of the original TAMe esterase activity. In this manner, activated PTA and plasma kallikrein have been shown to be distinct substances, and methods have been introduced for the further purification of active coagulation factor XI.